Comprehensive Characterization of Fly Ash as a Sustainable Supplementary Cementitious Material - Syahyadi, Rizal; Saidi, Taufiq; Hasan, Muttaqin; Akhyar; Fauzi, Amir; Rachman, Aulia (Salehan Institute of Higher Education, 2026)
Sustainable development seeks to meet present needs without harming future generations. Rising energy demand from coal-fired power plants increases CO₂ emissions and produces fly ash (FA). The cement industry, responsible for about 7% of global CO₂ emissions, also consumes large amounts of energy. Incorporating FA as a partial or complete substitute for cement in concrete provided both environmental and performance advantages. Hence, this study focused on exploring the potential of FA from Nagan Raya (FANR) as a cementitious material for cement replacement. FANR was analyzed using XRF, XRD, FTIR, SEM, and EDS. It mainly contained SiO₂ (48.04%), Al₂O₃ (27.62%), and Fe₂O₃ (11.78%), meeting ASTM Class F fly ash standards. XRD analysis confirmed the presence of amorphous phases along with quartz and mullite crystals. FTIR showed silicate hydration products (C–S–H and C–A–H gels) at different water–cement ratios. SEM showed spherical particles with rough surfaces, which enhance reactivity but also increase water absorption and reduce workability. EDS confirmed silicate and aluminosilicate compositions. These results highlight FANR’s potential as a sustainable cement replacement, despite workability issues.